Creating National Weights for a Patient-level Longitudinal Database - Onur Baser; Li Wang; Jon Maguire (Journal of Health Economics and Outcomes Research)
**Objective:** To create a nationally-representative estimate from longitudinal data by controlling for sociodemographic factors and health status.